Comment on Balsamo et al.: Birt-Hogg-Dubé syndrome with simultaneous hyperplastic polyposis of the gastrointestinal tract: case report and review of the literature - van de Beek, Irma; van Steensel, Maurice A. M.; Houweling, Arjan C. (BMC medical genomics, 2022)
The publication by Balsamo and colleagues describes a patient with Birt-Hogg-Dubé syndrome and hyperplastic polyposis throughout the gastro-intestinal tract. We question whether the diagnosis of BHD in this patient was justified. Using the previously proposed diagnostic criteria for establishing the diagnosis of BHD as a guideline, we systematically describe our concerns. In our opinion, the patient described by Balsamo and colleagues does not meet any of the proposed major and minor criteria for the diagnosis of Birt-Hogg-Dubé syndrome. Therefore, we believe that it is not justified to suggest a possible association between hyperplastic polyposis and Birt-Hogg-Dubé syndrome based on this patient, even though a higher risk for colorectal polyposis in Birt-Hogg-Dubé syndrome has not been excluded so far.